The Influence of Occupational Health on Operational Performance at the ACC Jakarta Air Traffic Service Centre - Edy Cahyono; Ichyu Machmiyana; Emilia Rahajeng Larasati (CV. AFDIFAL MAJU BERKAH, 2026)
This study investigates the influence of occupational health on operational performance among Air Traffic Controllers (ATCs) at the Area Control Centre (ACC) Unit of Jakarta Air Traffic Service Centre (JATSC). The research aims to identify how physical and mental health conditions such as fatigue, stress, and workload affect ATC performance in managing air traffic operations. Using a quantitative descriptive-correlational approach, data were collected through observation, documentation, and questionnaires distributed to 77 respondents selected purposively from a population of 238 ATCs. Data were analyzed using SPSS software, employing descriptive statistics, Pearson correlation, and multiple linear regression. The results show a significant positive relationship between occupational health and operational performance, with fatigue and stress emerging as dominant factors affecting performance levels. Healthy ATCs demonstrated higher alertness, communication accuracy, and decision-making speed, all of which are crucial for maintaining operational safety. The findings highlight that effective occupational health management contributes not only to individual well-being but also to the overall safety and efficiency of air navigation services. The study recommends that AirNav Indonesia enhance fatigue management systems and implement health-oriented scheduling policies to optimize controller performance and ensure sustainable aviation safety.